Object-oriented programming learning environment - Lipeikienė, Joana (Lietuvos matematikos rinkinys, 2001)
Various aspects of learning environments are discussed in the paper emphasizing the possibilities to improve teaching using them as a supplement of classroom-based teaching. Programming language C++ for Windows learning environment designed by the author is described.